An improved method for analyzing shear-lag in thin-walled girders with rectangular ribs. (February 2021) - Li, Shengyu; Hong, Yu; Gou, Hongye; Pu, Qianhui
Abstract: Because the traditional bar simulation method (BSM) cannot directly analyze the shear lag effect of thin-walled steel box girders with rectangular ribs on their top and bottom plates, this paper presents a new method to derive equivalent bar areas and governing differential equations to assess the shear lag effect. On the basis of this, an improved bar simulation method (I-BSM) is proposed for shear lag analysis. In addition, the paper analyzes the influence on the shear lag effect of the thickness of the top and bottom plates, the thickness of the rectangular ribs, and the height of the girder's cross-section. The results show that an increase in the thickness of the top and bottom plates will increase the shear lag effect of the top plate, but decrease the shear lag effect of the bottom plate. The thickness of the rectangular ribs, however, has little effect on the shear lag effect. An increase in the height of the cross-section will reduce the shear lag effect of the top plate and increase the shear lag effect of the bottom plate. In future, it is recommended to change the height of the cross-section and thickness of the top or bottom plate to adjust the shear lag effect while designing structures. The study also demonstrates the strong applicability of I-BSM as an effective approach to analyzing the shear lag effect of thin-walled steel box girders with rectangular ribs. Graphical abstract: Unlabelled Image Highlights: The improved bar simulation method (I-BSM) was proposed for analyzing the shear lag effect of the steel box girder. The result from the I-BSM proved the correctness of the normal stress distribution of the structure. The influence of the thickness of the rib on the shear lag effect of the steel box girder was analyzed based on the I-BSM. The influence of the thickness of the top and bottom plate on the shear lag effect was analyzed based on the I-BSM. The influence of the height of the cross-section on the shear lag effect was analyzed based on the I-BSM.